Effect of Aqueous Extract of Nigella Sativa seeds on Body Weight,Blood Glucose And Average Transit In Albino Rat Small Instestine - F. Kh. Tawfeek; Gh.A. Taqa (College of Education for Pure Sciences, 2005)
The study was conducted to shed some light on the effect ofthe aqueous extract of Nigella sativa seeds at dose 8g/kg bw daily for 15 days on body weight, blood glucose and the average intestinal transit in female immature rats. The results reveald a significant decrease in body weights of Nigella sativa treated rats compared with control, In addition , A significant decrease in blood glucose level, small intestinal transit was observed in rats treated with Nigella sativa_ seeds compared with the control group. The inhibitory effect of Nigella sativa aqueous extract on the small intestinal